1996
DOI: 10.1111/j.1432-1033.1996.0155t.x
|View full text |Cite
|
Sign up to set email alerts
|

A H2O‐Producing NADH Oxidase from the Protozoan Parasite Giardia Duodenalis

Abstract: We describe the purification of a H,O-producing NADH oxidase from the protozoan parasite Giardiu duodenalis. The enzyme is a monomeric flavoprotein containing flavin adenine dinucleotide in a 1 : 1 molar ratio with the polypeptide. The NADH oxidase has an apparent molecular mass of 46 kDa and was homogenous as determined by denaturing gel electrophoresis and N-terminal amino acid sequencing. NADPH could substitute for NADH as an electron donor with a K, value of 4.2 pM for NADH and 16 pM for NADPH (pH 7.8 at r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 51 publications
2
84
1
Order By: Relevance
“…Furazolidone resistance has also been induced in Giardia (22,195), and NADH oxidase has been shown to activate it to its free radical state (22,24). These lines were also more easily induced to quinacrine resistance, generating a second type of multidrug resistance (200).…”
Section: Giardia Drug Treatment and Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…Furazolidone resistance has also been induced in Giardia (22,195), and NADH oxidase has been shown to activate it to its free radical state (22,24). These lines were also more easily induced to quinacrine resistance, generating a second type of multidrug resistance (200).…”
Section: Giardia Drug Treatment and Resistancementioning
confidence: 99%
“…There is no evidence for O 2 utilization in Giardia, although O 2 has been shown to be consumed (110,229). Alternatively, it has been shown that O 2 can be converted directly to H 2 O by NADH oxidase to protect the key anaerobic enzymes in the glycolytic pathway, PFOR and ferredoxin, for example (22,24). These components have been purified and their activity has been demonstrated in vitro (194,196).…”
Section: Trichomonas Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…An Fe-type superoxide dismutase (SOD) has been described for H. inflata (Biagini et al, 1997) and, although SOD activity was initially reported in Giardia (Thompson et al, 1993), in a more recent study SOD activity was undetectable even after induction with 1,10-phenanthroline (Brown et al, 1995). In addition, G. intestinalis contains a thioredoxin-reductase-like disulphide reductase which has the ability to reduce cystine (Brown et al, 1996), whereas H. inflata contains an as yet uncharacterized thiol reductase which may be involved in cystine reduction (Biagini et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Both species lack catalase, glutathione and glutathione reductase ; moreover no superoxide dismutase (SOD) has been detected in G. lamblia (Brown et al, 1995). Proposed components of alternative mechanisms of oxygen detoxification (oxidation defence) in G. lamblia include a cytosolic H # O-forming NADH oxidase, proposed to function as a terminal oxidase that removes excess reducing equivalents and as a component of the electron-transport pathway that protects oxygenlabile proteins by maintaining a reduced intracellular environment (Brown et al, 1995(Brown et al, , 1996a(Brown et al, , 1998 ; a membrane-associated NADH peroxidase associated with the observed H # O # removal by viable trophozoites (Brown et al, 1995) ; and a thioredoxin-like disulfide reductase with a role in disulfide redox management (Brown et al, 1996b(Brown et al, , 1998.…”
Section: Introductionmentioning
confidence: 99%